(3Pjd GdTbGFb GdofYeGfjIs - (3Gdehdi HjQ eMeO GdTgjQ HYGTb LdHj Hf Ydj Hf Rjf GdYGHOjf GdfWGY GdHZOGOjs; (3WGTcHQj RGOI , YUGe GdOjf CHh GdNjQ CMeO Hf eUWaj Hf Ndjd, WGTcHQj RGOg,J (B968 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fRd GdaQbGf hJhdi MaXg s
(3BNQgG (B:s
(3hcGf UGMH CNdGb MejOg hcQe QhM Gddg QhMg hfhQ VQjMg s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B257s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B186 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs